Resistance to targeted therapies in chronic lymphocytic leukemia: Current status and perspectives for clinical and diagnostic practice - Blombery, Piers; Chatzikonstantinou, Thomas; Gerousi, Marina; Rosenquist, Richard; Gaidano, Gianluca; Pospisilova, Sarka; Roberts, Andrew W; Birkinshaw, Richard W; Rossi, Davide; Scarfo, Lydia; Seymour, John F; Stilgenbauer, Stephan; et al. (Leukemia, 2025)
The integration of BTK and BCL2 inhibitors into the treatment of patients with chronic lymphocytic leukemia (CLL) represents a paradigm shift and has led to significant improvements in clinical outcomes, including prolonged survival and enhanced quality of life. However, despite the efficacy of these agents, resistance to targeted therapy remains a major challenge, ultimately resulting in treatment failure and disease progression for a significant proportion of patients. Related to this, diagnostic testing for genetic variants associated with resistance, such as mutations in BTK, PLCG2 and BCL2, may become an increasingly common part of clinical routine practice. Addressing the need for placing the current knowledge in context, here we summarize the evidence from clinical studies and examine the underlying biology of both genetic and non-genetic resistance. Furthermore, we outline methodological approaches for the detection of gene alterations associated with targeted therapy resistance, discuss how to interpret these findings and highlight interpretation challenges. Finally, we offer insights into the clinical relevance of identifying genetic resistance to inform personalized treatment strategies and improve patient outcomes.
Keywords: Protein Kinase Inhibitors; Molecular Targeted Therapy; cílená molekulární terapie; chemorezistence; Leukemia, Lymphocytic, Chronic, B-Cell; Drug Resistance, Neoplasm; Mutation; mutace; lidé; Agammaglobulinaemia Tyrosine Kinase; protinádorové látky; chronická lymfatická leukemie; inhibitory proteinkinas; Humans; Antineoplastic Agents; proteinkinasa BTK